Киллер: [роман] / Павел Астахов - Астахов Павел Алексеевич (Астахов, 2016)
Экземпляры: СБ (20160518) / Инвентарный номер: 52189 / Цена: 265.00 / Сис.шифр: Р2 / Авт.знак: А 91 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6